Desarrollo De Un Programa De Gobierno De Datos Para Merccap Sa: Reforzando La Seguridad De La Información (2023)
In the context of MercCap, the importance of data governance is evident in the need to ensure the quality, security, and accessibility of information. The organization has distinguished itself as a provider of pricing data in the Colombian financial market, and to maintain and enhance its leadership position in the future, it is essential to implement a data governance program.